The effect of liquid bound by microparticles (ions) on the membrane selectivity - Poliakov, V.L. (Доповіді НАН України, 2023)
Notion “critical concentration” was introduced for membrane processes, and a formula was proposed to calculate it. A mathematical problem of steady-state convective-diffusive mass transfer within the layer of concentration polarization was formulated and exactly solved, taking into account the hydration of microparticles (ions). For numerous examples, analyses were performed to estimate the effect of hydration and mass transfer parameters on the concentration of suspended microparticles at the membrane surface and its selectivity for uniform impurity.